Low-dose Sevoflurane Attenuates Cardiopulmonary Bypass (CPB)- induced Postoperative Cognitive Dysfunction (POCD) by Regulating Hippocampus Apoptosis via PI3K/AKT Pathway - Qin, Jianhua; Ma, Qingjun; Ma, Dongmei (Current Neurovascular Research, 2020)
Background: Cardiopulmonary bypass (CPB) caused postoperative cognitive dysfunction (POCD) was characterized by hippocampus apoptosis, which seriously limited the therapeutic efficacy and utilization of CPB in clinic. Recent data indicated that sevoflurane anesthesia might alleviate CPB-induced POCD, however, the underlying mechanisms are still unclear. Methods: In the present study, the in vivo CPB-POCD models were established by using aged Sprague-Dawley (SD) male rats and the in vitro hypoxia/reoxygenation (H/R) models were inducted by using the primary hippocampus neuron (PHN) cells. Results: The results showed that CPB impaired cognitive functions and induced hippocampus apoptosis in rat models, which were alleviated by pre-treating rats with low-dose sevoflurane. In addition, the phosphatidylinositol 3 kinase (PI3K)/protein kinase B (AKT) signal pathway was inactivated in the hippocampus tissues of CPB-POCD rats, which were rescued by low-dose sevoflurane treatment. Of note, the PI3K/AKT inhibitor (LY294002) abrogated the protective effects of low-dose sevoflurane on CPB-POCD rats. Consistently, the in vitro results showed that H/R treatment induced cell apoptosis and inhibited cell viability in PHN cells, which were attenuated by low-dose sevoflurane. Similarly, LY294002 abrogated the inhibiting effects of low-dose sevoflurane on H/R-induced PHN cell death. Conclusion: Taken together, low-dose sevoflurane attenuated CPB-induced POCD by inhibiting hippocampus apoptosis through activating PI3K/AKT signal pathway.
Keywords: heart surgery